L’apport de la gestion intégrée des zones côtières (GIZC) à la gestion de l’érosion côtière : intérêt et exemple en Méditerranée française - Hélène Rey-Valette; Philippe Carbonnel; Sébastien Roussel; Alexandre Richard (VertigO)
This paper studies to the contribution of Integrated Coastal Zone Management (ICZM) to coastal erosion management. The analysis of coastal erosion management policies underlines three logics towards integrated approaches. Since coastal defence policies have promoted the construction of hard structures in order to deal with local effects, coastal erosion has been managed at a broader scale; thus, the complexity of coastal issues can be dealt with. The aim is to take into account interdependencies based on regional management schemes in order to define sediment cells, and change the way coastal erosion is tackled through beach nourishment or realignment policies. Furthermore, the aim is to integrate stakeholder representations and local governance systems in these coastal issues. With this prospect, this paper analyses how ICZM principles could be practically applied to coastal erosion management while detailing ICZM implementation conditions with their gradual, flexible and concerted features. The significance of voluntary approaches regarding bottom-up approaches for ICZM implementation is also stressed. This could be developed for coastal erosion through environmentally friendly guidelines and sustainable tourism regarding beach carrying capacity. Moreover, a relevant scale has to be designed from the governance point of view in order to prevent domino effects from uses and pressures between territories. Lastly, a case study is proposed through the example of the beaches of the town of Villeneuve-lès-Maguelone (Région Languedoc-Roussillon, Département de l’Hérault, France). To cope with the loss of the lido, an integrated management project is currently underway and is coordinated by the Département de l’Hérault as a part of the BEACHMED-e INTERREG III-C South European project (2005-2008). This depicts the significance of combining the analysis of sediment cells and territory scales, as well as defining several areas for integrating local particularisms and adapting scenarios to the diversity of issues and zones.